Embedding public participation in service delivery planning in South Africa - France K.L. Kgobe; Mohamed S. Bayat; Abdulrazak Karriem (Journal of Local Government Research and Innovation)
Background: In the past 30 years, South Africa has prioritised public participation in service delivery planning as a cornerstone of democratic governance by using forums and meetings to integrate citizen input. This commitment is backed by legal frameworks to enhance public service standards and ensure community voices are represented in local governance process.